2023
DOI: 10.3390/su15020971
|View full text |Cite
|
Sign up to set email alerts
|

The Coupling and Coordination of Agricultural Carbon Emissions Efficiency and Economic Growth in the Yellow River Basin, China

Abstract: The balanced ecological protection and high-quality development of the Yellow River basin (YRB) has become a major national strategy in China in which low-carbon agricultural development in the region is crucial. In this context, studying the coupling and coordination between agricultural carbon emissions efficiency and economic growth in the YRB is of great significance to promote low-carbon, green, and sustainable agricultural development. Therefore, based on the data of 30 cities in the YRB from 2010 to 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…At present, research on the elements of the Yellow River Basin system mainly includes water, energy and food 63 , low-carbon development and eco-environment 65 , sustainable development and environmental protection 66 , water utilization, industrial development and ecological welfare 67 , urbanization and water resource 78 , urbanization and ecosystem service value 79 , ecology and economy 80 , resources, economy and ecosystem 81 , human settlement environment and tourism industry 82 , public health, ecological environment and economic development 83 . agricultural carbon emissions efficiency and economic growth 84 , tourism, ecological-environment and public service 85 . This study found that the CCD values in the FES system of the Yellow River Basin showed an increasing trend, ranging from 0.53 to 0.87 for flood-sediment transportation, eco-environment, and socio-economy.…”
Section: Discussionmentioning
confidence: 99%
“…At present, research on the elements of the Yellow River Basin system mainly includes water, energy and food 63 , low-carbon development and eco-environment 65 , sustainable development and environmental protection 66 , water utilization, industrial development and ecological welfare 67 , urbanization and water resource 78 , urbanization and ecosystem service value 79 , ecology and economy 80 , resources, economy and ecosystem 81 , human settlement environment and tourism industry 82 , public health, ecological environment and economic development 83 . agricultural carbon emissions efficiency and economic growth 84 , tourism, ecological-environment and public service 85 . This study found that the CCD values in the FES system of the Yellow River Basin showed an increasing trend, ranging from 0.53 to 0.87 for flood-sediment transportation, eco-environment, and socio-economy.…”
Section: Discussionmentioning
confidence: 99%
“…From 2010 to 2020, Henan Province's ACEE and degree of food security were assessed using Super-E cient SBM (based on the relaxation model) and the Comprehensive Index Method (Gu et al 2023). The ultrae cient slack measure (SBM) model of unexpected output was utilized to effectively measure the ACEE of the YRB based on data from 30 cities from 2010 to 2020 (Qing et al 2023). Furthermore, when considering the features of temporal and spatial evolution, spatial analysis methods, such as kernel density estimation and the primary purpose of spatial autocorrelation, are used to investigate the temporal and geographical variations and convergence of the ACEE.…”
Section: Literature Reviewmentioning
confidence: 99%
“…DID models and comparative studies were employed [36]. To effectively measure agricultural carbon emission efficiency in the Yangtze River Delta, an ultra-efficient relaxation-based measurement (SBM) model with unexpected outputs was used [37]. Scholars have performed research from the national, provincial, or a localized development region, depending on the scope of the study.…”
Section: Literature Reviewmentioning
confidence: 99%